KOMUNIKASI POLITIK MENGGUNAKAN ARTIFICIAL INTELLIGENCE (AI ) DALAM KAMPANYE PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN 2024 PADA KEMENANGAN PRABOWO – GIBRAN DI PROVINSI RIAU - Nainggolan, Enjelia Priskila; Susanto, Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study discusses political communication using Artificial Intelligence (AI) technology in the 2024 Presidential and Vice Presidential Election campaign that led to the victory of the Prabowo Subianto-Gibran Rakabuming Raka pair in Riau Province. The research method used was a descriptive qualitative approach, with data collection techniques through in-depth interviews, documentation, and literature studies. The results show that the use of Artificial Intelligence (AI) in the Prabowo-Gibran presidential and vice presidential campaign was able to increase the effectiveness of political messaging, personalize campaign content, and mobilize young voters in Riau Province. The Artificial Intelligence (AI)-based campaign utilized big data to map voter preferences, optimize social media algorithms, and create a political image relevant to the digital community. Despite bringing innovation and strategic advantages, the use of Artificial Intelligence (AI) in political campaigns also raises ethical and regulatory challenges, particularly regarding the potential for manipulating public opinion. Therefore, the use of AI technology in the political sphere must be conducted ethically, transparently, and responsibly to maintain the integrity of democracy. Keywords : Political Communication, Artificial Intelligence (AI), Political Campaigns, Prabowo-Gibran, Riau Province